Decrease of evoked delta, theta and alpha coherences in Alzheimer patients during a visual oddball paradigm - Güntekin, Bahar; Saatçı, Ertuğrul; Yener, Görsev (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
In this study event related coherence of patients with Alzheimer type of dementia (AD) was analyzed by using a visual oddball paradigm as stimuli. A total of 21 mild probable AD subjects (10 untreated, 11 treated) were compared with a group of 19 healthy controls. The members of the groups had their EEG recorded from 12 electrodes by means of a visual oddball paradigm. The evoked coherence was analyzed for delta (1-3.5 Hz), theta (4-7 Hz) and alpha (8-13 Hz) frequency ranges for inter-hemispheric (F(3)-F(4), C(3)-C(4), T(3)-T(4), T(5)-T(6), P(3)-P(4), O(1)-O(2)) and long range intra-hemi spheric (F(3)-P(3), F(4)-P(4), F(3)-T(5), F(4)-T(6), F(3)-O(1), F(4)-O(2)) electrode pairs. The control group showed higher values of evoked coherence in "delta", "theta" and "alpha" bands in the left fronto-parietal electrode pairs in comparison with the untreated AD group (p < 0.01 for all frequency bands). Furthermore, the control group showed higher values of evoked coherence in the left fronto-parietal electrode pair in theta frequency band (p < 0.01) and higher values of evoked coherence in the right fronto-parietal electrode pair in delta band (p < 0.01) when compared to treated AD group. The only significant difference between the treated and untreated AD groups was in the alpha band. The treated AD group showed higher values of evoked coherence at the left fronto-parietal pair in alpha band in comparison to the untreated AD group (p < 0.01). During a working memory process the coherence in the left fronto-parietal electrode pair (F(3)-P(3)) of AD patients is significantly decreased, thus indicating reduced connectivity between frontal and parietal sites. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: alzheimer; evoked coherence; oddball paradigm; event related oscillations; recorded eeg-epograms; neurofibrillary tangles; functional connectivity; reticular-formation; cognitive decline; combined dynamics; auditory pathway; senile plaques; cat brain; disease; alzheimer; uyarılmış tutarlılık; tuhaf paradigma; olaya ilişkin salınımlar; nörofibrillerin; fonksiyonel bağlantı; retiküler oluşumu; bilişsel gerileme; kombine dinamikleri; işitsel yolu; senil plaklar; kedi beyni; hastalık